Increasing Productivity of Egg Production through Individual Selection on Tegal Ducks (Anas javanicus) - Ismoyowati, Ismoyowati; Suswoyo, I; Sudewo, ATA; Santosa, SA (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2009)
The purpose of this research was to study the effect of egg production selection characteristic on productivity of Tegal duck. Materials used were 112 of six month old Tegal ducks consisted of 16 males and 96 females. Selection for females was applied on 12 duck groups based on egg production phenotipic: parent stock duck (G1) which was offspring of their ancestor (G0) having egg production above average production (not less than 78 eggs in 120 days); while the males were selected based on egg production of their mother, and 4 groups were use as control. Production and reproduction data were analysed descriptively compared to initial population using T test. Egg production was analysed based on Nested Classification to estimate haritability value (h2). The results indicated that egg production increased from 78.00±19.00 (G0) to 88.12±11.57 (G1). Heritability estimation on egg production and genetic progress were 0.35 and 5.95 respectively. On the male, the selection increased body weight and semen quality. It was concluded that selection of egg production characteristics increased productivity of Tegal duck. (Animal Production 11(3): 183-188 (2009) Key Words : selection, heritability, body statistic, egg production, Tegal duck